Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.20408/jti.2020.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes and Recurrence in Chronic Subdural Hematoma Patients Treated by Burr-Hole Drainage with or without Irrigation

Abstract: Purpose: Chronic subdural hematoma (CSDH) is a common disease in elderly patients and is usually treated by burr-hole drainage. However, the optimal surgical technique for treating CSDH has not been determined. In this study, we analyzed outcomes and recurrence rates after burr-hole drainage with or without irrigation in patients with CSDH. methods: Eighty-two CSDH patients treated with burr-hole drainage at Wonju Severance Christian Hospital from March 2015 to June 2016 were enrolled in this study. The subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Intraoperative saline irrigation has been reported to significantly reduce CSDH recurrence compared with no irrigation in prior studies. [28][29][30] Moreover, the amount of saline irrigation has noteworthy importance for reducing recurrent rates when at least 3,200 mL of saline was used by the HR plot. Initially, we analyzed this variable as a continuous variable and found that the amount of saline irrigation significantly affected a reduction of risk of recurrence (HR: 0.99, 95% CI: 0.992-0.998 in multivariable analysis).…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative saline irrigation has been reported to significantly reduce CSDH recurrence compared with no irrigation in prior studies. [28][29][30] Moreover, the amount of saline irrigation has noteworthy importance for reducing recurrent rates when at least 3,200 mL of saline was used by the HR plot. Initially, we analyzed this variable as a continuous variable and found that the amount of saline irrigation significantly affected a reduction of risk of recurrence (HR: 0.99, 95% CI: 0.992-0.998 in multivariable analysis).…”
Section: Discussionmentioning
confidence: 99%
“…CSDH is generally a condition affecting the elderly after mild trauma. 2 7 13 17 29) and while it can be completely cured with surgery, there is a high rate of postoperative relapse. 2 15) The postoperative prognosis for CSDH is diverse and there have been various studies on the factors affecting prognosis during treatment after the initial diagnosis of CSDH.…”
Section: Discussionmentioning
confidence: 99%
“…CSDH has low morbidity and mortality after surgical intervention. 2 15) Nevertheless, the relapse rate is an important factor in the prognosis of patients with CSDH. There have been several previous studies on CSDH relapse.…”
Section: Discussionmentioning
confidence: 99%